Abiotic Stress in Plants 2021
DOI: 10.5772/intechopen.94563
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Water Stress on Growth, Chlorophyll Contents and Solute Accumulation in Three Accessions of Vicia faba L. from Tunisian Arid Region

Abstract: In this study, we aim to investigate the physiological and biochemical adaptations of Vicia faba plants to moderate irrigation regime (T1) and describe the effects of water stress on their growth performance and chlorophyll contents. For this reason, three Tunisia accessions (ElHamma, Mareth and Medenine) were studied. An experiment was conducted for one month. Faba bean plants were first grown in a greenhouse and then, exposed to water stress, whereby they were irrigated up to the field capacity (FC) of 0% (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…The rosemary and cistus responded in a similar way to water deficit with a decrease in total chlorophyll content (Fig. 4) due to the increased degradation of photosynthetic pigments (Enneb et al 2020) and to the death of some cells (Fig. 5h) due to the low plant LWC (Table 1: 59% ± 3 and 62% ± 4 respectively for rosemary and cistus leaves).…”
Section: Discussionmentioning
confidence: 86%
“…The rosemary and cistus responded in a similar way to water deficit with a decrease in total chlorophyll content (Fig. 4) due to the increased degradation of photosynthetic pigments (Enneb et al 2020) and to the death of some cells (Fig. 5h) due to the low plant LWC (Table 1: 59% ± 3 and 62% ± 4 respectively for rosemary and cistus leaves).…”
Section: Discussionmentioning
confidence: 86%
“…However, the temporal responses of the four VIs were not significantly different from one another, although the PSSRa and PRI indices responded more quickly than the others ( Figure 4B ). The earlier decrease in PSSRa might be a result of an increase the catalytic activity of chlorophylls and degradation of photosynthetic pigments (Enneb et al, 2020). The decrease in Chl content is a commonly observed phenomenon under drought stress (Ashraf & Harris, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This decrease could be due to direct damage of the chloroplast in the presence of glyphosate, as plants from all maturity groups exposed to a single or sequential application of glyphosate frequently had chlorophyll concentrations lower than plants that were not exposed to this herbicide. It's also well known that a decrease in the chlorophyll content could be due to a decrease in the stomata aperture, aimed at limiting water losses by evaporation and by increased resistance to the entry of atmospheric CO 2 necessary for photosynthesis (Zhu et al, 2016;Enneb et al, 2020). Karabulut and Çanakcı (2021) showed that the oxidative stress created by glyphosate treatment caused decrease in chlorophyll (a+b).…”
Section: Degradation Of Chlorophyll Contentmentioning
confidence: 99%